2014
DOI: 10.1177/0022022114532353
|View full text |Cite
|
Sign up to set email alerts
|

Intended Self-Presentation Tactics in Job Interviews

Abstract: Intended self-presentation in job interviews was examined among university students in 10 countries (N = 3,509). The aim was to assess cross-cultural differences in the endorsement of self-presentation tactics, and whether such differences could be explained by cultural values and socioeconomic variables. The Cultural Impression Management Scale–Applicant Scale (CIM-A) was used that measures assertiveness, individual excellence, accommodation, and pointing out obstacles. Cross-cultural differences were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 54 publications
2
38
0
4
Order By: Relevance
“…exaggerating skills, de‐emphasising negative attributes, portraying oneself as more agreeable) among applicants in four countries, König et al () showed that prevalence rates in Iceland and Switzerland were substantially lower than those in China and the US. Sandal et al () surveyed students from 10 countries in terms of the importance they assigned to several self‐presentation tactics (expressing excellence, mentioning external obstacles, and stressing assertiveness and accommodation), and found indications of culturally and economically caused differences. In a survey of employees from 31 countries, Fell et al () revealed substantial country‐level relationships between attitudes toward (mild/severe forms of) applicant faking and cultural dimensions of the Global Leadership and Organisational Behavior Effectiveness project (GLOBE; House et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…exaggerating skills, de‐emphasising negative attributes, portraying oneself as more agreeable) among applicants in four countries, König et al () showed that prevalence rates in Iceland and Switzerland were substantially lower than those in China and the US. Sandal et al () surveyed students from 10 countries in terms of the importance they assigned to several self‐presentation tactics (expressing excellence, mentioning external obstacles, and stressing assertiveness and accommodation), and found indications of culturally and economically caused differences. In a survey of employees from 31 countries, Fell et al () revealed substantial country‐level relationships between attitudes toward (mild/severe forms of) applicant faking and cultural dimensions of the Global Leadership and Organisational Behavior Effectiveness project (GLOBE; House et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To demonstrate the robustness and external validity of the hypothesised relationship between faking and CWs, we tested it in different samples and cultural contexts, controlling for various individual differences and context factors that were previously identified as correlates of faking, and using different measures of faking. Examining the robustness of the CWs–faking relationship in different cultural contexts is particularly important in light of recent studies that suggest that applicants from different cultures have different attitudes towards faking (Fell, König, & Kammerhoff, ) and that faking frequency can be influenced by cultural or socioeconomic factors (König, Wong, & Cen, ; Sandal et al, ). More specifically, in our studies, we tested the relationship between CWs and faking intentions controlling for individual differences with respect to the dark triad of personality in a sample of job applicants in the US (Study 1).…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…International Test Commission, ; Ryan & Tippins, ) emphasise the importance of considering societal culture in the design and implementation of selection tools, including practices such as establishing equivalence of measures across cultures (Hambleton, ; Meade & Lautenschlager, ), conducting reviews of test content for cultural sensitivity (Brislin, ), and assessing applicant reactions cross‐culturally (Ryan et al, ; Steiner & Gilliland, ). Specifically, much has been written about how societal culture may influence the acceptance and use of testing (Fell, König, & Kammerhoff, ; Fell & König, : Lim, Chavan, & Chan, ; Ryan et al, ; Ryan, McFarland, Baron, & Page, ; Sandal et al, : Steiner & Gilliland, ). This issue of where there is societal cultural variability in selection tool use and acceptance is particularly important from a practical side, as it can affect whether resources are devoted to developing culturally specific assessments and policies versus using more globally‐standard approaches, as well as heighten or reduce concerns regarding practice effectiveness in different locations.…”
Section: Introductionmentioning
confidence: 99%